2012
DOI: 10.1371/journal.pone.0033729
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Let-7 Up-Regulates EZH2 in Prostate Cancer Consistent with the Acquisition of Cancer Stem Cell Signatures That Are Attenuated by BR-DIM

Abstract: The emergence of castrate-resistant prostate cancer (CRPC) contributes to the high mortality of patients diagnosed with prostate cancer (PCa), which in part could be attributed to the existence and the emergence of cancer stem cells (CSCs). Recent studies have shown that deregulated expression of microRNAs (miRNAs) contributes to the initiation and progression of PCa. Among several known miRNAs, let-7 family appears to play a key role in the recurrence and progression of PCa by regulating CSCs; however, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
164
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(172 citation statements)
references
References 48 publications
8
164
0
Order By: Relevance
“…Lineage-mapping studies have identified epigenetic dysregulation as a critical early event in human tumorigenesis (24), supporting the concept of an epigenetic progenitor origin of cancer (22). Furthermore, cells with CSC features appear molecularly dissociable from non-CSCs (25)(26)(27)(28)(29), and animal models have demonstrated that epigenetic interventions can reduce CSC frequencies and attenuate tumorigenesis (30,31). For instance, microRNAs suppressing the expression of members of the polycomb repressive complex-2 (PRC2), including Let-7 and the miR200 family, are downregulated in CSC-containing fractions of breast and prostate cancer whereas increased levels were observed in non-stem cancer cells (25,28,29).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Lineage-mapping studies have identified epigenetic dysregulation as a critical early event in human tumorigenesis (24), supporting the concept of an epigenetic progenitor origin of cancer (22). Furthermore, cells with CSC features appear molecularly dissociable from non-CSCs (25)(26)(27)(28)(29), and animal models have demonstrated that epigenetic interventions can reduce CSC frequencies and attenuate tumorigenesis (30,31). For instance, microRNAs suppressing the expression of members of the polycomb repressive complex-2 (PRC2), including Let-7 and the miR200 family, are downregulated in CSC-containing fractions of breast and prostate cancer whereas increased levels were observed in non-stem cancer cells (25,28,29).…”
Section: Introductionmentioning
confidence: 84%
“…Furthermore, cells with CSC features appear molecularly dissociable from non-CSCs (25)(26)(27)(28)(29), and animal models have demonstrated that epigenetic interventions can reduce CSC frequencies and attenuate tumorigenesis (30,31). For instance, microRNAs suppressing the expression of members of the polycomb repressive complex-2 (PRC2), including Let-7 and the miR200 family, are downregulated in CSC-containing fractions of breast and prostate cancer whereas increased levels were observed in non-stem cancer cells (25,28,29). Accordingly, the expression of PRC2 members SUZ12 and EZH2 was shown to be upregulated in CSC-enriched fractions of breast and prostate tumors (25,29).…”
Section: Introductionmentioning
confidence: 99%
“…Aberrantly expressed miRNAs can cause deregulation of specific signaling pathways that are associated with the functions of CSCs. Particularly, miR-34 family or let-7 family [50,51] have been involved in the regulation of PCa CSC properties.…”
Section: Role Of Mirnas In Prostate Cancermentioning
confidence: 99%
“…Several miRNA negatively regulate EZH2 expression, for example, miRNA-101, miRNA-26a, miR-29, and miR-214 negatively regulate EZH2 during various differentiation processes. 56 Furthermore, downregulation of miRNA is frequently associated with abnormally elevated levels of EZH2 in cancer; for instance, the downregulation of miR-25 and miR30d is involved in thyroid carcinoma 57 , let-7 in prostate cancer, 58 miR-98 and miR-214 in esophageal squamous cell carcinoma, miR26a and miR-29 in rhabdomyosarcoma. 59,60 Post-translational modifications of EZH2 PRC2 activity can be regulated by post-translational modifications that are able to control the recruitment of target genes and/or its catalytic activity.…”
Section: Transcriptional Regulation Of Prc2mentioning
confidence: 99%